Energy partitioning and spatial variability of air temperature, VPD and radiation in a greenhouse tunnel shaded by semitransparent organic PV modules. (15th May 2021) - Friman-Peretz, Maayan; Ozer, Shay; Levi, Asher; Magadley, Esther; Yehia, Ibrahim; Geoola, Farhad; Gantz, Shelly; Brikman, Roman; Levy, Avi; Kacira, Murat; Teitel, Meir
Highlights: Experiments were done in a greenhouse tunnel covered by organic photovoltaics (OPVs). Spatial variability due to the nonhomogeneous shading by OPVs is studied. Comparison is made with a greenhouse tunnel shaded by a shading net (control). Spatial variability of air temperature and VPD was similar to the control. Shading by OPVs virtually did not affect the energy partitioning. Abstract: A study related to the application of organic photovoltaic (OPV) modules in greenhouses is presented. It considers the impact of nonhomogeneous shading by semitransparent OPV modules, placed on the cover of a greenhouse tunnel housing a tomato crop, on energy partitioning and the spatial variability of radiation, air temperature and vapour pressure deficit (VPD) within the tunnel. Experiments were conducted in two similar tunnels covered by a diffuse polyethylene sheet. Flexible semitransparent strips of OPV modules were placed on 37% of the roof area of one tunnel, creating an approximately 23% nonhomogeneous shading, while the other tunnel, homogeneously shaded by a 25% black shading net, served as a control greenhouse. The results show that on cloudy days (high diffuse radiation), spatial variability of radiation in the OPV tunnel was smaller than on sunny days (low diffuse radiation). Conversely, variability in air temperature and VPD did not change much with the change in diffuse radiation. Except when diffuse radiation was high, no significant difference in the energy partitioning between nonhomogeneous shading by OPVs and homogeneous shading was observed. Most of the net radiation in the tunnels was converted into latent heat. With a high solar elevation angle, the spatial variability of radiation within the tunnel was higher than with a low solar elevation angle. Additional experiments are needed to determine the best arrangement of semitransparent OPV modules on the roof, without resulting in any significant increase in spatial variability. Agronomic aspects of plant growth under the OPV modules are briefly presented.